Work-family balance, employee commitment, and number of dependents among staff in a malaysian tv network / Shereen Noranee …[et al.] - Noranee, Sherreen; Mohd Said, Hanan; Zainuddin, Anizah; Abdul Aziz, Rozilah; Abdul Munir, Zarina (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, 2017)
Committed employees tend to perform better as they feel having personal connection towards the organization. However, in some cases, dismissal from the organization also indicates poor job performance. Poor job performance resulted in low organizational commitment. The ability of an individual to balance between work and family depends on several factors such as the type of job, the organization that hires them, economy, social and cultural context. The emerging situation had led to overload of responsibility as people had to play the role of employees, spouses, parents, and parent's caregivers. Biased participation in one role, either work of family, will affect the other role. Work-family balance has two types of relationship. The first relationship is when work interferes with family life and the second relationship is when family life interferes with work. The main purpose of this study was to examine the effect of work-family balance towards employee commitment among TVABC (a Malaysian television network) staff, with number of dependents as moderating variable. The responses were gathered from 184 TVABC staff. Convenient sampling technique was used and hierarchical regression analysis was administered. The results indicated that work interference with family dimension did not had any significant relationship with employee commitment. While family interference with work was proven to have a significant relationship with employee commitment among TVABC staff. The number of dependents, as the moderating variable, was found not affecting the relationship between work-family balance and employee commitment as all tests indicated insignificant relationship.